OPERATIONAL RISK MANAGEMENT OF AN INDEPENDENT ISLAMIC BANK - Miftachus Surur; Firnanda Ayu Widiyanita (IAIN Batusangkar, 2021)
Risk is always be an obstacle to achieving the goals of companies and financial institutions,both of conventional and sharia. It has become a necessity for every company and financial institutionto have a good risk management system so be able to manage existing risks in order to avoid losses, butthe application of risk management carried out by Islamic banks certainly has a very high complexityand needs to be deepen. This study uses a qualitative descriptive approach with purposive sampling ofreports on the implementation of BSM operational risk management and the efforts made to mitigaterisk in 2016-2019. Syari'ah Mandiri Bank has the aim to create sustainable company growth through theoptimization of Good Corporate Governance (GCG). Based on the Risk & Control Self Assessment (RCSA)assessment, operational risks that occurred in BSM from 2016 to 2019 have been successfully managed wellwith the average impact rating low moderate - moderate and average frequency level 2 (The possibility ofan event occurring in a 12 month period of less than 20%), this shows that achievement of the applicationoperational risk management that has been very well done by Syari 'ah Mandiri Bank.